Analysis of the chloroplast crotonylome of wheat seedling leaves reveals the roles of crotonylated proteins involved in salt-stress responses. (11th January 2023) - Zhu, Dong; Liu, Junxian; Duan, Wenjing; Sun, Haocheng; Zhang, Liping; Yan, Yueming
Abstract: Lysine crotonylation (Kcr) is a novel post-translational modification and its function in plant salt-stress responses remains unclear. In this study, we performed the first comprehensive chloroplast crotonylome analysis of wheat seedling leaves to examine the potential functions of Kcr proteins in salt-stress responses. In a total of 471 chloroplast proteins, 1290 Kcr sites were identified as significantly regulated by salt stress, and the Kcr proteins were mainly involved in photosynthesis, protein folding, and ATP synthesis. The identified Kcr sites that responded to salt stress were concentrated within KcrK and KcrF motifs, with the conserved KcrF motif being identified in the Kcr proteins of wheat chloroplasts for the first time. Notably, 10 Kcr sites were identified in fructose-1, 6-bisphosphate aldolase (TaFBA6), a key chloroplast metabolic enzyme involved in the Calvin–Benson cycle. Site-directed mutagenesis of TaFBA6 showed that the Kcr at K367 is critical in maintaining its enzymatic activity and in conferring salt tolerance in yeast. Further molecular dynamic simulations and analyses of surface electrostatic potential indicated that the Kcr at K367 could improve the structural stability of TaFBA6 by decreasing the distribution of positive charges on the protein surface to resist alkaline environments, thereby promoting both the activity of TaFBA6 and salt tolerance. Abstract : Lysine crotonylation at the K367 site improves the structural stability of FBA6 in wheat chloroplasts under salt stress, thereby promoting its activity and enhancing salt tolerance